Cognitive And Psychoemotional Disorders In Patients With Hypothyreosis - Shokhrukh R. Rakhimberdiev, Gulnara S. Rakhimbaeva (International Journal of Advanced Science and Technology, 2020)
Thyroid pathology with full right to be considered as a marker of environmental problems, since none of the varieties of endocrine pathology is related to the environment, like thyroid disease. Hypothyroidism is a common thyroid syndrome that affects all organs and the body system. Thus, the purpose of the study is to identify the nature of neurological complications in patients with correction possibilities. All patients complained of dizziness, which was mainly of an unsystematic nature, headaches, memory loss, distraction, drowsiness, numbness in the arms and legs of one degree or another, a feeling of "crawling creeps," which usually developed at night and in the morning, and when performing monotonous work. The severity of pain of one or another localization was insignificant and did not exceed two points on a scale analogue scale.